Carbon dots nanozyme for anti-inflammatory therapy via scavenging intracellular reactive oxygen species - Dong, Chen; Ma, Xuehua; Huang, Yi; Zhang, Yujie; Gao, Xiang (Frontiers in Bioengineering and Biotechnology, 2022)
Developing an efficient antioxidant for anti-inflammatory therapy via scavenging reactive oxygen species (ROS) remains a big challenge owing to the insufficient activity and sustainability of conventional antioxidants. Herein, we explored and simply synthesized a biocompatible carbon dots (CDs) nanozyme with excellent scavenging activity of ROS for anti-inflammatory therapy. As expected, CDs nanozyme effectively eliminate many kinds of free radicals including •OH, O2•−, and ABTS+•. Benefiting from multienzyme activities against ROS, CDs nanozyme can decrease the levels of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), resulting in good anti-inflammatory effect. Taken together, this study not only sheds light on design of bioactive antioxidants but also extends the biomedical application of CDs for anti-inflammatory treatment.